Country Partnership Framework for the Republic of Croatia for the Period of FY19-FY24 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2019)
Croatia is a small, open economy and the latest entrant to the European Union. After being severely affected by the global financial crisis, Croatia’s economy is recovering, with growth averaging around three percent over the last four years. The over-arching objective of the WBG Country Partnership Framework (CPF) is to play a catalytic role in supporting institutional improvements needed for a sustainable trajectory towards EU convergence and eventual IBRD graduation. This CPF would support interventions to address Croatia’s climate vulnerabilities and protect its natural environment. This would be achieved primarily through ongoing and prospective advisory services, but also through potential WBG investments, including from IFC, and potentially from MIGA guarantees. The CPF will cover a five-year period (FY19-24) with one Progress and Learning Review (PLR). This approach includes a relatively narrow results framework that builds primarily on the ongoing portfolio and the nature of RAS-financed engagements. The PLR would provide an update on key areas of institutional weakness, including to measure progress against EU peers where benchmarks are available. While the WBG may contribute only modestly to these outcomes, it expects to play a catalytic role, and monitoring outcome indicators which are comparable across the EU will be particularly important to track progress in the areas on the critical path to accelerate convergence.